New information on the bar-tailed godwit Limosa lapponica (Linnaeus, 1758) and red-throated diver Gavia stellata (Pontoppidan, 1763) on the Crimean Peninsula (the Black Sea) - V. E. Giragosov (A. O. Kovalevsky Institute of Biology of the Southern Seas of RAS, 2021)
New data on the distribution of the bar-tailed godwit Limosa lapponica (Linnaeus, 1758) and red-throated diver Gavia stellata (Pontoppidan, 1763) on the Crimean Peninsula are presented. Against the backdrop of aquatic and coastal ecosystems’ transformation under natural and anthropogenic impact, even single finds of hydrophilic avifauna representatives in atypical spatiotemporal conditions are of interest for the analysis of emerging trends in migration phenology and abundance of both separate species and taxonomic and ecological groups of birds. The aim of the study was to clarify the distribution boundaries and terms of stay on the Crimean Peninsula of two hydrophilic bird species: semiaquatic species, bar-tailed godwit, and true water bird, red-throated diver. Bird observations were carried out during scheduled accountings on the Isthmus of Ak-Monay (March 2012) and in the Kruglaya Bay (Sevastopol) (July 2019). The bar-tailed godwit is registered in Crimea during spring and autumn migration periods. For the first time, it was found in the north of the Crimean Peninsula in 1972; later, there were an increase in its abundance and expansion of a distribution area. Recent records of this species in southern Crimea significantly expanded the known boundaries of its distribution on the peninsula during the migration period. The observation of the bar-tailed godwit in eastern Crimea on 14 March, 2012, specified the date its spring migration begins; the observation in Sevastopol (western foothill) on 27 July, 2019, was the first one in Mountain Crimea. Off the Crimean coast, the red-throated diver is a rare overwintering and migratory bird. The find of the red-throated diver individual in the Kruglaya Bay on 19 January, 2020, was the third reliable record of this species overwintering in Crimea and the first one in Sevastopol area. The registration of the red-throated diver at a considerable distance from its usual overwintering areas (off the southwestern coast of the Black Sea), along with numerous facts of the expansion of nesting or winter ranges of different bird species northward, confirms the ongoing climatic and ecological changes. Particular attention should be focused on the problem, associated with low ecological culture of the use and disposal of fishing tackles, which have a detrimental effect on hydrophilic birds. Measures have to be developed to regulate fishing with nets, hooks, and line tackles in the areas of bird mass overwintering and seasonal migrations.